The forkhead transcription factor FoxY regulates Nanos - Song, Jia L. (2012)
FoxY is a member of the forkhead transcription factor family that appeared enriched in the presumptive germ line of sea urchins (Ransick et al., 2002, Dev Biol 246:132). Here we test the hypothesis that FoxY is involved in germ line determination in this animal. We found two splice forms of FoxY that share the same DNA-binding domain but vary in the carboxy-terminal trans-activation/repression domain. Both forms of the FoxY protein are present in the ovary and in the early embryo, and their mRNAs accumulate to their highest levels in the small micromeres and adjacent non-skeletogenic mesoderm. Knockdown of FoxY resulted in a dramatic decrease in the Nanos mRNA and protein levels as well as a loss of coelomic pouches in the 2-week-old larvae. Our results indicate that FoxY positively regulates Nanos at the transcriptional level and is essential for reproductive potential in this organism.